PENAMPILAN DAN PRODUKSI KARKAS ITIK LOKAL JANTAN (Anas platyrhynchos)YANG DIBERI PAKAN MENGANDUNG TEPUNG LIMBAH RUMPUT LAUT (Eucheuma cottonii) FERMENTASI - Pratama, indra; Fatmawaty, Fatmawaty; Sulistiawati, Dwi (AgriSains, 2012)
The objective of the research is to know the effects of the fermented-seaweed meal waste available in the ration to the performance (weight gain, consumption and convertion of ration, carcass production (carcass percentage, carcass components, and abdominal fat). This research applied 80 local day oldduck (DOD). The research design applied was Completely Randomized Design (CRD) consisting of 4 treatments which were repeated for 5 times. Every repetition consists of 4 local duck. The treatments applied were: R0 = Controlled Ration, R1 = Ration containing of 2,5%fermented-seaweed meal waste. R2 = Ration containing of 5% fermented-seaweed meal waste, and R3 = Ration containing of 7,5% fermented-seaweed meal waste.The result of this research shows that the treatments hadnot significant influence on the duck performance and abdominal fat, butsignificantly influence on the percentage of carcass and the carcass components, whileÂ  abdominal fat decreaseto the higher fermented seaweed meal waste contained in the ration. Key words: Abdominal fat, carcass component, consumption, convertion of ration carcass, local duck, waste seaweed fermented, weight gain.